JUAL BELI APARTEMEN CASA GRANDE RESIDENCE OLEH PASANGAN SUAMI ISTERI YANG BERBEDA KEWARGANEGARAAN: Sale And Purchase Of Casa Grande Residence Apartments By Married Couples With Different Nationalities - Wijayanti, Mayday Hanura; Setiawati, Anda (AMICUS CURIAE, 2024)
Based on Article 33 paragraph (3) of the 1945 Constitution, every Indonesian has the right to benefit from existing land in Indonesia, including to meet the need for a place to live. However, times are changing and the population is increasing, including foreigners working in Indonesia. For foreigners, they are given flats built on usufructuary land. In relation to the purchase of apartments, the law also limits the purchase of flats/apartments for husband and wife who are of different nationalities and do not have a separate property agreement, where they are only allowed to buy flats built on land with a usage right. Married couples of different nationalities can buy a flat on HGB land if prior to the marriage they entered into an agreement to separate assets. With the decision of the Constitutional Court Number 69/PUU-XIII/2015, married couples of different nationalities can enter into an agreement to separate assets after the marriage takes place and can buy flats built on HGB land.